Mental Health-Friendly Pesantren Management Model: Implementation of Psychological First Aid (PFA) Based on Tawakkul and Tahajud Values - Akhmat Fanani Ridho (Pascasarjana Manajemen Pendidikan Islam STAI Darussalam Nganjuk, Indonesia, 2026)
Background: Mental health challenges among santri (Islamic boarding school students) in Indonesia are increasingly recognized, yet many pesantren lack structured psychosocial support systems. Psychological First Aid (PFA) offers a promising framework for initial crisis intervention, but its integration with Islamic spiritual values remains underexplored. Objective: This study aims to develop a management model for mental health-friendly pesantren through the implementation of PFA grounded in the Islamic values of tawakkul (trust in Allah) and tahajud (night prayer). Method: This qualitative study employs a grounded theory approach. Data were collected through in-depth interviews, participant observation, and document analysis involving pesantren administrators, caregivers, santri, and mental health practitioners in selected pesantren in [location]. Data analysis followed the Corbin and Strauss (2015) grounded theory procedure. Findings: The study identified three core categories: (1) integration of tawakkul as a psycho-spiritual coping mechanism, (2) tahajud as a psychophysiological intervention for stress reduction and emotional regulation, and (3) a five-phase PFA implementation model adapted to pesantren contexts. Conclusion: A substantive theory of Psycho-Spiritual First Aid Management is proposed, offering a culturally and spiritually congruent framework for mental health-friendly pesantren management.